A Comparison of Cardiac Computed Tomography, Transesophageal and Intracardiac Echocardiography, and Fluoroscopy for Planning Left Atrial Appendage Closure - Osmancik, Pavel; Herman, Dalibor; Linkova, Hana; Hozman, Marek; Labos, Marek (Journal of atrial fibrillation, 2021)
BACKGROUND: Left atrial appendage (LAA) closure (LAAC) is accompanied by a high risk of complications. Due to the complex anatomy of the LAA and the oval-shaped ostium, the proper sizing of the device is often difficult. PURPOSE: To assess individualized fluoroscopy viewing angles using pre-procedural CT analysis and to compare the results of landing zone measurements obtained from CT, transesophageal echocardiography (TEE), intracardiac echocardiography (ICE), and fluoroscopy. METHODS: Patients with indications for LAAC were enrolled. Cardiac CT and TEE were done before the procedure; ICE and fluoroscopy measurements were done peri-procedurally. Multiplanar reconstruction of CT images, using FluoroCT software, was done, and optimal "personalized" viewing angles for fluoroscopy were determined. Moreover, a mean (using multiplanar CT reconstruction, derived from the LAA perimetr) amd maximum (using all four imaging modalitities) landing zone (LZ) of the LAA were masured. RESULTS: Twenty-five patients were analyzed. Despite significant correlation between LZs obtained from different imaging modalities, the values of LZs differed significantly; the mean LZ diameter on CT was 20.60 ± 3.42 mm, the maximum diameters were 21.99 ± 4.03 mm (CT), 18.72 ± 2.44 mm (TEE), 18.20 ± 2.68 mm (ICE), and 17.76 ± 3.24 mm (fluoroscopy). The mean CT diameter matched with the final device selection in 92% patients, while fluoroscopy or TEE maximum diameters in only 72% patients. Optimal viewing angles differed significantly from the fluoroscopy projections usually recommended by the manufacturer in 3 patients. CONCLUSIONS: CT provides the best measurement of the LZ and the best prediction of the optimum fluoroscopy projections for the implantation procedure.
Keywords: Computed Tomography; Intracardiac Echocardiography; Atrial Fibrillation; Transesophageal Echocardiography; Left Atrial Appendage Closure